Oral cancer in non-smoker non-drinker patients. Could comparative pet oncology help to understand risk factors and pathogenesis?. (October 2021) - Grigolato, Roberto; Accorona, Remo; Lombardo, Giorgio; Corrocher, Giovanni; Garagiola, Umberto; Massari, Federico; Nicoli, Stefano; Rossi, Sabrina; Calabrese, Luca
Highlights: Oral cancer in non-smoker non-drinker patients has been increasing in incidence over the last decades. Adequate study models to analyze this entity are still lacking. Companion animals share the same environment of humans; moreover, they are exposed to many of the same risk factors. Spontaneous oral cancer in pets can be a useful study model for oral cancer in non-smoker non-drinker patients. Abstract: During the last decades there has been a progressive increase in proportion of incidence of oral cancer not related to a known etiologic factor, such as the so-called "oral cancer in young", a relevant tumor in non-smoker non-drinker (NSND) patients. The topic is matter of long standing debate, and adequate study models to analyze this entity are lacking. Spontaneous oral cancer in companion animals such as dogs and cats, presents more clinical and biological similarities with the human oral cancer than any other animal model. In our review we analyze how the study of spontaneous oral cancer in common pets can prospectively prove to be of double usefulness in unraveling the question about the origin of oral cancer in NSND patients, allowing both the analysis of environmental and behavioral risk factors, and the study of how carcinogenic viruses, chronic inflammation, and changes in immunity can influence pre-tumoral and tumoral microenvironment.